The role of a nested polymerase chain reaction in the diagnosis of Pneumocystis carinii pneumonia. Issue 6 (December 1995) - Evans, R; Joss, A W L; Parratt, D; Pennington, T H; Ho-Yen, D O
Abstract : Aim —To compare the techniques and results of a nested PCR and an immunofluorescence assay (IFA) for the detection of Pneumocystis carinii infection; to consider the role of the nested PCR in the diagnosis of P carinii pneumonia (PCP). Methods —Serial dilutions of two known P carinii positive samples were tested by IFA and PCR to determine their relative sensitivities. Seventy eight respiratory samples (15 from 11 patients with HIV infection/acquired immunodeficiency syndrome (AIDS) and 63 from 42 patients with other forms of immunodeficiency) were tested using both assays, and the costs and technical requirements of each assay were assessed. Results —The PCR had a greater relative sensitivity over the IFA of 2 × 10 1 to 2 × 10 3 fold in a postmortem lung sample and 2 × 10 5 to 2 × 10 6 fold in a bronchoalveolar lavage sample from a patient with PCP. P carinii was detected in all 15 samples from the patients with HIV/AIDS by both IFA and PCR. Of the 63 samples from the patients with immunodeficiencies other than HIV/AIDS, the PCR was more sensitive than IFA. Conclusions —The nested PCR is a more sensitive assay than the IFA. It may be useful in the diagnosis of PCP in patients with immunodeficiencies other than HIV/AIDS. Similarly, PCR may be of benefit for this patient group as less invasive specimens are needed. PCR has an increasing role to play in the diagnosis of PCP in the routine laboratory.